Social representations of transsexual prostitution - Granillo, Lissette Yamile; Cruz Flores, Ivonne Janeth; Aguilar Macías, Arturo Misael (Sekkan Revista de Ciencias Sociales y Humanidades, 2025)
Prostitution is rarely discussed and, for transsexual women, it is a stigmatized topic and, therefore, marginalized from considered normal behavior. This practice addresses the stigmatization and commercialization of women and reinforces sexist inequality, reinforcing the emphasis on the objectification of women’s bodies, forming a Social Representation frequently experienced by them through exclusion by those who do not belong to the sector. The feminist approach given is important to investigate the fact that transsexual women in prostitution receive a certain stigmatization for their trade and sexual identity, that results in exclusion and social marginalization led by prejudices brought by social discourses with a certain amount of power, which is experienced over them. One discipline that allows us to analyze this phenomenon is social psychology, because it helps us to understand human relationships and the interaction of prostitutes within society. This research sought to theorize and reflect on the phenomenon in relation to society, politics and morality, through critical theory and using a descriptive analysis with the phenomenological method based on in-depth interviews, to carry out a system of analysis of categories that allowed us to answer the research question. This analysis shows that discrimination is not simply because they are sex workers, but rather, it begins when these women ascribe to a sexual identity different from what is considered normative, which reduces their employment options and forces them to “choose” the option with the least risk.
Keywords: Discrimination; feminism; prejudice; stigmatization; reification